APLIKASI E-GOVERNMENT DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK PADA BEBERAPA PEMERINTAH DAERAH KOTA/KABUPATEN DI INDONESIA - Ely Sufianti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2007)
The implementation of e-Government for better public service delivery has recently attracted government agents. This research aims at finding out the availability and types of services electronically provided by local governments. From 22 local government websites, it is revealed that the websites mostly display one-way announcement/information regarding demography and licensing services. Only few display interaction menu, provide two way/interactive page, and/or alredy possess transaction page.